Some Varieties of Quasigroups, Loops and their Parastrophes - Plaumann, P.; Sabinina, L.; Sbitneva, L. (Communications in Mathematics and Applications, 2012)
The role of the parastrophes in the theory of quasigroups and loops is well known. It is our approach to investigate remarkable classes of loops and quasigroups and to relate them to their parastrophes. Some consequences for code loops are presented.
Keywords: Quasigroup; Loop; Parastrophe